2010
DOI: 10.1002/adma.200904270
|View full text |Cite
|
Sign up to set email alerts
|

Elastomeric Conductive Composites Based on Carbon Nanotube Forests

Abstract: Highly elastic and electrically conductive composite sheets are prepared by infiltration of MWNT forests with polyurethane binder. After initial pretreatment, the composite provides highly reproducible changes in resistivity at elongations up to 40%. Almost no degradation in electrical properties and a linear dependence of resistivity on strain is observed for strains in 10%–20% range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
290
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(301 citation statements)
references
References 19 publications
7
290
1
3
Order By: Relevance
“…Another method is to embed or bond rigid and active electronic components into a soft rubbery polymer. 2,10,[17][18][19][20] For example, Shin et al 17 fabricated elastomeric conductive composites by the infiltration of multiwalled carbon nanotube forests with a polyurethane binder. Someya's group developed highly conductive, printable and stretchable composite films using ionic liquid, fluorinated copolymer and ultralong single-walled carbon nanotubes (SWNTs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method is to embed or bond rigid and active electronic components into a soft rubbery polymer. 2,10,[17][18][19][20] For example, Shin et al 17 fabricated elastomeric conductive composites by the infiltration of multiwalled carbon nanotube forests with a polyurethane binder. Someya's group developed highly conductive, printable and stretchable composite films using ionic liquid, fluorinated copolymer and ultralong single-walled carbon nanotubes (SWNTs).…”
Section: Introductionmentioning
confidence: 99%
“…11,19 Although mechanical stretchability was successfully achieved, most of the above studies demonstrated that the resistance of the obtained composites increases rapidly with tensile strain (4100% increase of resistance at 100% strain). 5,10,11,17,18 Very recently, a new strategy was developed for generating stretchable conductors by backfilling an infinite connected network of conducting fillers (such as single-walled carbon nanotubesaerogels 21 or graphene foams 22 ) with an elastic polymer. Owing to the prefabricated three dimensional (3D) network structures, these composites showed a relatively high electrical conductivity and electromechanical stability under stretching and bending.…”
Section: Introductionmentioning
confidence: 99%
“…These materials can be produced through the heat treatment (pyrolysis) of aligned nanofiber polymer matrix nanocomposite (A-PNC) precursors, which are analogous to the APNCs reported elsewhere [15][16][17][18][19][20][21][22][23][24] . Such processing follows the typical synthesis routes of polymer derived ceramics [25][26][27][28] , but relies on capillary [15][16][17][18][19][20][21] or vacuum [21][22][23][24] assisted wetting of the aligned nanofibers rather than surfactant or functionalization assisted mixing. In order to manufacture aligned nanofiber carbon matrix nanocomposites (A-CMNCs) with tailored properties, the porosity of the matrix, which strongly influences its material properties, must be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several studies have shown that CNTs networks can be formed within polymers to yield highly conductive and stretchable strain sensors 22, 207, 208, 216, 218, 219. In one paramount study, SWCNTs were embedded into a stacked nanohybrid structure within polyurethane (PU)–PEDOT:PSS to provide a transparent, stretchable, and patchable strain sensor 208.…”
Section: Conductive Polymer Compositesmentioning
confidence: 99%